LINGUISTIC, COGNITIVE, AND METHODOLOGICAL PROBLEMS AFFECTING LISTENING COMPREHENSION (SCIENCE TIME JOURNAL, 2026)
This article examines the linguistic, cognitive, and methodological problems that affect listening comprehension in English language learning. Listening comprehension is considered one of the most complex receptive skills because it requires the simultaneous processing of phonological, lexical, grammatical, semantic, pragmatic, and contextual information. The study discusses listening comprehension not only as the passive reception of sound but also as an active cognitive process involving perception, parsing, interpretation, prediction, memory, attention, and metacognitive control. The article analyzes major linguistic barriers such as speech rate, connected speech, reduced forms, unfamiliar vocabulary, accent variation, intonation, and discourse structure. It also explores cognitive difficulties related to working memory, attention distribution, anxiety, lack of background knowledge, and limited use of listening strategies. Methodological problems, including insufficient pre-listening preparation, overreliance on testing rather than teaching listening, lack of authentic materials, and ineffective feedback, are also examined. The article concludes that listening comprehension can be improved through systematic strategy instruction, metacognitive awareness, authentic input, staged listening tasks, and learner-centered teaching approaches.